Quadratus Lumborum Block in Caesarean Section: A Case Report - Harsakti Rasyid; Nur Surya Wirawan (HM Publisher, 2022)
Introduction: Quadratus lumborum (QLB) block is a posterior abdominal wall block (interfascial plane block) with ultrasound guidance. This study describes the administration of quadratus lumborum block as pain management on C-section. Case presentation: A woman, 31 years old, G2P1A0 post-C-section 4 years ago, is planning to undergo elective C-Section surgery. Vital sign examination within normal limits. The patient was included in the ASA II category. Prior to surgery, the patient was given premedication in the form of omeprazole 40 mg intravenously, paracetamol 1 gram intravenous drip for 15 minutes, and metoclopramide 10 mg intravenously. Quadratus lumborum block was given postoperatively. Postoperative management consisted of ibuprofen 800 mg/8 hour drip for 30 minutes and paracetamol 750 mg/6 hour drip. Conclusion: Pain management with the QLB method reduces postoperative acute pain and recovery. Further studies with a wider population are needed to explore the efficacy and effectiveness of QLB blocks.